The Influence of Collaborative Learning Models in Increasing Elementary School Students’ Creativity and Motivation - Sanasintani Sanasintani (Yayasan Adra Karima Hubbi, 2024)
Background. Collaborative learning is increasingly being implemented in elementary schools as an alternative to increase student creativity and motivation. However, the challenges and obstacles in its implementation need to be considered to understand its impact on learning effectiveness. Teachers should have many methods to make students happier and receive lessons well Purpose. This research aims to investigate the effect of the collaborative learning model on increasing student creativity and motivation at the elementary school level in West Sumatra. The main focus is to understand teachers’ perceptions of this model, identify the obstacles faced, and evaluate its effectiveness. Method. The research method used was a quantitative survey with 20 teachers from several elementary schools in West Sumatra district as respondents. Data collection was carried out through distributing questionnaires designed to measure teachers’ perceptions of the collaborative learning model, as well as its impact on student creativity and motivation. Data analysis used the Miles and Huberman approach. Results. Analysis of the questionnaire results showed that the majority of teachers (75%) strongly agreed that the collaborative learning model had great potential to increase student creativity and motivation. However, the main challenge identified was the limited time in the established curriculum. Conclusion. Although the collaborative learning model is considered effective, teacher support and understanding needs to be improved through additional training. Strategic adjustments are also needed to overcome the constraints of time constraints and individual evaluations, as well as to understand more deeply differences in student skill levels. Overall, this learning model has great potential in increasing student motivation and creativity in elementary school, provided it is expanded and better supported by educators.